IL‐22 and IL‐22‐Binding Protein Are Associated With Development of and Mortality From Acute‐on‐Chronic Liver Failure. Issue 3 (17th January 2019) - Schwarzkopf, Katharina; Rüschenbaum, Sabrina; Barat, Samarpita; Cai, Chengcong; Mücke, Marcus M.; Fitting, Daniel; Weigert, Andreas; Brüne, Bernhard; Zeuzem, Stefan; Welsch, Christoph; Lange, Christian M.
Abstract : Interleukin‐22 (IL‐22) has context‐dependent hepatoprotective or adverse properties in vitro and in animal models. IL‐22 binding protein (IL‐22BP) is a soluble inhibitor of IL‐22 signaling. The role of IL‐22 and IL‐22BP in patients with acute‐on‐chronic liver failure (ACLF) is unclear. Beginning in August 2013, patients with liver cirrhosis with and without ACLF were prospectively enrolled and followed at predefined time points. IL‐22 and IL‐22BP concentrations were quantified and associated with clinical endpoints. The impact of IL‐22BP on hepatocellular IL‐22 signaling was assessed by functional experiments. A total of 139 patients were analyzed, including 45 (32%), 52 (37%), and 42 (30%) patients with compensated/stable decompensated liver cirrhosis, acute decompensation of liver cirrhosis, and ACLF at baseline, respectively. Serum levels of IL‐22 and IL‐22BP were strongly associated with the presence of, or progression to, ACLF ( P < 0.001), and with mortality ( P < 0.01). Importantly, the mean IL‐22BP levels exceeded IL‐22 levels more than 300‐fold. Furthermore, IL‐22BP/IL‐22 ratios were lowest in patients with adverse outcomes (i.e., ACLF and death). In vitro experiments showed that IL‐22BP at these concentrations inhibits hepatocellular IL‐22 signaling, including the induction of acute‐phase proteins. The capacity of patient serum to induce signal transducer and activator of transcription 3 phosphorylation was substantially higher in the presence of low versus high IL‐22BP/IL‐22 ratios. Conclusion: Our study reveals that high IL‐22 levels and low ratios of IL‐22BP/IL‐22 are associated with ACLF and mortality of patients with cirrhosis. Excessive secretion of IL‐22BP can neutralize IL‐22 in vitro and may prevent—likely in a context‐specific manner—hepatoprotective, but also adverse effects, of IL‐22 in patients with cirrhosis. Abstract : Our study reveals that high IL‐22 levels and low ratios of IL‐22BP/IL‐22 are associated with ACLF and mortality of patients with cirrhosis. Excessive secretion of IL‐22BP can neutralize IL‐22 in patients with liver cirrhosis and may prevent – likely in a context‐specific manner – hepatoprotective, but also adverse effects of IL‐22.